Addictive platforms - Shota Ichihashi; Byung-Cheol Kim (Bank of Canada, 2022)
We study competition for consumer attention, in which platforms can sacrifice service quality for attention. A platform can choose the "addictiveness" of its service. A more addictive platform yields consumers a lower utility of participation but a higher marginal utility of allocating attention. We provide conditions under which increased competition can harm consumers by encouraging platforms to offer low-quality services. In particular, if attention is scarce, increased competition reduces the quality of services because business stealing incentives induce platforms to increase addictiveness. Restricting consumers' platform usage may decrease addictiveness and improve consumer welfare. A platform's ability to charge for its service can also decrease addictiveness.
Keywords: D40; L51; 330; Economic models